The Photosystem II Assembly Factor Ycf48 from the Cyanobacterium Synechocystis sp. PCC 6803 Is Lipidated Using an Atypical Lipobox Sequence - Knoppová, Jana; Yu, Jianfeng; Janouškovec, Jan; Halada, Petr; Nixon, Peter J; Whitelegge, Julian P; Komenda, Josef (International journal of molecular sciences, 2021)
Photochemical energy conversion during oxygenic photosynthesis is performed by membrane-embedded chlorophyll-binding protein complexes. The biogenesis and maintenance of these complexes requires auxiliary protein factors that optimize the assembly process and protect nascent complexes from photodamage. In cyanobacteria, several lipoproteins contribute to the biogenesis and function of the photosystem II (PSII) complex. They include CyanoP, CyanoQ, and Psb27, which are all attached to the lumenal side of PSII complexes. Here, we show that the lumenal Ycf48 assembly factor found in the cyanobacterium Synechocystis sp. PCC 6803 is also a lipoprotein. Detailed mass spectrometric analysis of the isolated protein supported by site-directed mutagenesis experiments indicates lipidation of the N-terminal C29 residue of Ycf48 and removal of three amino acids from the C-terminus. The lipobox sequence in Ycf48 contains a cysteine residue at the -3 position compared to Leu/Val/Ile residues found in the canonical lipobox sequence. The atypical Ycf48 lipobox sequence is present in most cyanobacteria but is absent in eukaryotes. A possible role for lipoproteins in the coordinated assembly of cyanobacterial PSII is discussed.
Keywords: bakteriální proteiny; Photosystem II Protein Complex; Synechocystis; photosynthesis; chlorophyll-binding proteins; photosystem II; Bacterial Proteins; metabolismus lipidů; fotosystém II (proteinový komplex); Lipid Metabolism